Personalized Baghdadite scaffolds: stereolithography, mechanics and in vivo testing. (15th September 2021) - Mirkhalaf, Mohammad; Dao, Aiken; Schindeler, Aaron; Little, David G.; Dunstan, Colin R.; Zreiqat, Hala
Abstract: An ongoing challenge in the field of orthopedics is to produce a clinically relevant synthetic ceramic scaffold for the treatment of 'critical-sized' bone defects, which cannot heal without intervention. We had developed a bioactive ceramic (baghdadite, Ca₃ZrSi₂O₉) and demonstrated its outstanding bioactivity using traditional manufacturing techniques. Here, we report on the development of a versatile stereolithography printing technology that enabled fabrication of anatomically-shaped and -sized Baghdadite scaffolds. We assessed the in vivo bioactivity of these scaffolds in co-delivering of bone morphogenetic protein-2 (BMP2) and zoledronic acid (ZA) through bioresorbable coatings to induce bone formation and increase retention in a rat model of heterotopic ossification. Micro-computed tomography, histology, mechanical tests pre- and post-implantation, and mechanical modelling were used to assess bone ingrowth and its effects on the mechanics of the scaffolds. Bone ingrowth and the consequent mechanical properties of the scaffolds improved with increasing BMP2 dose. Co-delivery of ZA with BMP2 further improved this outcome. The significant bone formation within the scaffolds functionalized with 10 µg BMP2 and 2 µg ZA made them 2.3 × stiffer and 2.7 × stronger post-implantation and turned these inherently brittle scaffolds into a tough and deformable material. The effects of bone ingrowth on the mechanical properties of scaffolds were captured in a mechanical model that can be used in future clinical studies for non-destructive evaluation of scaffold's stiffness and strength as new bone forms. These results support the practical utilization of our versatile stereolithographic printing methods and BMP2/ZA functionalization to create fit-for-purpose personalized implants for clinical trials. Statement of significance: In this study, we addressed a long-standing challenge of developing a ceramic printing technology that enables fabrication of customizable anatomically-shaped and -sized bioceramic scaffolds with precise internal architectures using an inexpensive desktop printer. We also addressed another challenge related to delivery of pharmaceuticals. BMP2, currently available as a bone-inducing bioactive protein, is clinically administered in a collagen scaffold that has limited moldability and poor mechanical properties. The comparably stiffer and stronger 3D printed personalized Baghdadite scaffolds developed here can be readily functionalized with bioresorbable coatings containing BMP2 ± ZA. These innovations considerably improve on the prior art and are scalable for use in human surgery. Graphical abstract: Image, graphical abstract